Associations of ultra‐processed food and drink products with asthma and wheezing among Brazilian adolescents. Issue 5 (29th May 2018) - Melo, B.; Rezende, L.; Machado, P.; Gouveia, N.; Levy, R.
Abstract: Background: Although both consumptions of ultra‐processed products and asthma are common during adolescence, the epidemiological evidence in regarding their association is unclear. We investigated the associations of ultra‐processed products consumption with asthma and wheezing in a representative sample of Brazilian adolescents. Methods: We used data from a representative sample of 109 104 Brazilian adolescents enrolled in the National Survey of School Health, 2012. The consumption of ultra‐processed products was based on the weekly consumption (0‐2, 3‐4, ≥5 d/wk) of sweet biscuits, salty biscuits, ultra‐processed meats, sweets/candies, soft drinks, and packaged snacks over the previous 7 days. We also calculated an ultra‐processed consumption score by adding partial scores corresponding to weekly frequency intake of each ultra‐processed product. The ultra‐processed consumption score ranged from 0 to 42, the higher score, the higher the intake of these products. The presence of wheezing in the previous 12 months and asthma at any time in the past was self‐reported. Results: The adjusted odds ratios of asthma comparing the extreme categories ranged from 1.08 (95% CI 1.03‐1.13) for sweets/candies to 1.30 (1.21‐1.40) for ultra‐processed meats. Similar magnitude of associations was found for wheezing outcome. The ultra‐processed consumption score was positively associated with the presence of asthma and wheezing in a dose‐response manner. The adjusted OR of asthma and wheezing comparing highest to lowest quintile of ultra‐processed consumption score was 1.27 (95% CI 1.15‐1.41) and 1.42 (1.35‐1.50), respectively. Conclusions: The consumption of ultra‐processed products was positively associated with the presence of asthma and wheezing in adolescents.